Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw untuk Meningkatkan Hasil Belajar pada Mata Pelajaran Pendidikan Pancasila Siswa Kelas Vll C Di SMPN 5 Lembar - Jaelani, Hermanto; Ismail, M.; Samsul Hadi, M. (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to improve student learning outcomes in the Pancasila Education subject for class VII-C at SMPN 5 Lenbar by implementing the Jigsaw cooperative learning model. The method used was a qualitative approach through classroom action research (CAR), conducted in three cycles, each consisting of one session. The research subjects included 29 students and a Pancasila Education teacher. Data were collected through observation, tests, and documentation, and were analyzed descriptively. The action was initiated due to students’ low learning outcomes, which were attributed to monotonous teaching methods. In the initial stage, only 7 students (60%) met the minimum mastery criteria (KKM), while 12 students (40%) had not yet achieved mastery. The findings showed an improvement in learning outcomes across each cycle. In the first cycle, mastery was achieved by 17 students (59%), which increased to 23 students (80%) in the second cycle, and in the third cycle, all 29 students (92%) successfully achieved mastery. This improvement demonstrates that the implementation of the Jigsaw cooperative learning model is effective in enhancing student learning outcomes, as a result of collaboration between the teacher and the researcher throughout the learning process.